Design Methodology of Energy Storage Systems for a Small Electric Vehicle - Trovão, João P. (2009)
With the current state of technological development, the future of Electric Vehicles (EVs) seems to go through the hybridization of various Energy Storage Systems (ESSs). This strategy seeks to benefit from the best qualities of each available energy source, and is especially useful in urban driving. In this work, the need for multiple energy sources hybridization is addressed. A methodology to optimize the sizing of the ESSs for an electric vehicle taking as example the ISEC-VEIL project, using different driving cycles, maximum speed, a specified acceleration, energy regeneration and gradeability requests are presented. It is also studied the possibility of using a backup system based on solar energy, that may be considered in the design, or as an extra to cope with unforeseen routines and to minimize the recharge of ESSs. Some simulation results of multiple energy sources hybridization are presented, considering different ESSs and different scenarios for the small presented EV, in order to verify the proposed designs.